Developmental coordination disorder: “It’s not on people’s radars… They’re not interested” - Rebecca Murray; Cara E. Staniforth; Amira Shawak; Lucy H. Eddy (PLoS ONE, 2025)
Background Developmental Coordination Disorder (DCD) is an under-recognised neurodevelopmental disorder impacting 5–6% of children. There is plentiful research exploring the deleterious impacts of poor motor skill development, however there is a distinct lack of research gathering in-depth insights which explore the impact of DCD across life domains and the life course. Methods Ten lived experience interviews (parents of a child with a diagnosis of DCD) were undertaken online, lasting 30–45 minutes. Participants were recruited both nationally and internationally to understand cultural differences. Parent interviews focused on experiences in primary care, education, friendships, and wellbeing. Data were transcribed and analysed using inductive thematic analysis. Results Identified major themes highlighted (i) impact of DCD on the lives of children and their families; (ii) lack of knowledge and awareness surrounding DCD; (iii) inadequate support; and (iv) the role of diagnosis. All of this culminated in parents feeling the need to become advocates in the face of a profound sense of relative abandonment. Conclusion Children with DCD and their families face multiple profound challenges in relation to accessing help and support for their difficulties. More needs to be done to facilitate synergistic support for children with DCD and their families across healthcare, education and the wider community. Effective cross-sector care will however, not be possible without the development of evidence-based training for all, which is underpinned by insider voices.